Teaching in the Digital Era: Teachers’ Adaptation in an Entirely Online World - Sanasintani, Sanasintani (EduTech Journal, 2025)
This study aims to describe the adaptation process of teachers in responding to the shift from conventional to digital learning systems in an increasingly online era, specifically focusing on junior high school teachers in Yogyakarta City. The rapid changes brought about by technological advancement and the pandemic situation have required teachers to integrate technology into their daily teaching practices. This research employs a descriptive quantitative method, with data collected through questionnaires distributed to 50 teachers. The results show that the majority of teachers are able to operate digital devices and platforms such as Google Classroom, Zoom, and other learning applications. However, challenges remain, including limited infrastructure, a lack of targeted training, and low student participation in online learning. Support from schools and a collaborative culture among teachers have proven to be highly beneficial in this adaptation process. This study highlights the importance of enhancing digital literacy and the need for educational policies that are responsive to the challenges of 21st-century learning.